2015
DOI: 10.1370/afm.1819
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Led, Empowerment-Based Approach to Self-Management Efforts in Diabetes (PLEASED): A Randomized Controlled Trial in an African American Community

Abstract: PURPOSE We compared a 3-month diabetes self-management education (DSME) program followed by a 12-month peer support intervention with a 3-month DSME program alone in terms of initial and sustained improvements in glycated hemoglobin (HbA 1c ). Secondary outcomes were risk factors for cardiovascular disease (CVD), diabetes distress, and social support. METHODSWe randomized 106 community-dwelling African American adults with type 2 diabetes to a 3-month DSME program followed by 12 months of weekly group sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 26 publications
9
116
1
3
Order By: Relevance
“…We found that DSME based individual program was conducted into 40.9% of the studies (12,13,16,20,23,25,29,30,32) and 59.1% of the studies offered the DSME in a combination of individual and group education (12,14,15,17,20,21,27,31,32,34) . In general, The individual or group-based program provided the intervention of several strategies, including personalized counseling, feedback regarding goal-setting and problem-solving, support for self-care practice from family members, and the follow-up session.…”
Section: Diabetes Mellitus Self-management Education (Dsme)mentioning
confidence: 99%
See 4 more Smart Citations
“…We found that DSME based individual program was conducted into 40.9% of the studies (12,13,16,20,23,25,29,30,32) and 59.1% of the studies offered the DSME in a combination of individual and group education (12,14,15,17,20,21,27,31,32,34) . In general, The individual or group-based program provided the intervention of several strategies, including personalized counseling, feedback regarding goal-setting and problem-solving, support for self-care practice from family members, and the follow-up session.…”
Section: Diabetes Mellitus Self-management Education (Dsme)mentioning
confidence: 99%
“…Four studies used food model, picture, illustration, foot picture (14,18,20,24) . Diabetes handout/booklet (diet, exercise, medication, eye, and foot self-care) been used to spread the knowledge (15,16,19,21,30,32,36) . In addition, four studies (13,14,20,34) used video and DVD to show the successfully of self-care behaviors practice among diabetes patients.…”
Section: Education Materialsmentioning
confidence: 99%
See 3 more Smart Citations